Distributive justice in network communications. (20th September 2019) - Moktan, Gautam Raj; Manner, Jukka
Communication networks often have limited resources to serve all users and flows, and therefore different network resource assignment schemes have been deployed that satisfy fairness notions such as max-min fairness or proportional fairness. The justification of why one notion suits over other must be given due analysis in designing and administrating of communication networks. We explore the development of such fairness notions and resource assignment policies from philosophical and economics roots and how they translate into network communications and its layered protocol architecture. We find that resource assignment policies are not commutative, which impacts communications traffic and its bidirectional nature. We observe the effect of prioritisation in assigned resource amounts under different notions of the α -fairness spectrum and when the proportion of prioritised participants is varied. After an exploratory discourse, we formulate steps for designing and administrating resource allocation schemes for network communications that takes distributive justice into consideration.